2018
DOI: 10.31878/ijcbr.2018.43.08
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ionized Calcium Status in Febrile Seizures

Abstract: Introduction: Epilepsy is one of the most common disorders of the brain. One of every ten people will have at least one epileptic seizure during a normal lifespan, and a third of these will develop epilepsy. In children the most common forms of convulsion are febrile seizures. Water electrolyte imbalance occurs during acute febrile illness and hypocalcaemia is one of them. Hypocalcaemia is also present in cases of seizures. To find out significance of calcium levels in cases of seizures this study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In another study from Maharashtra, no correlation was found between low serum calcium levels and febrile seizures [8]. Another Indian study has reported a significantly low ionized calcium levels in children [9]. Similar studies have also been conducted in other parts of the world and a similar association between low serum calcium levels and febrile seizures was found [5].…”
Section: Discussionmentioning
confidence: 86%
“…In another study from Maharashtra, no correlation was found between low serum calcium levels and febrile seizures [8]. Another Indian study has reported a significantly low ionized calcium levels in children [9]. Similar studies have also been conducted in other parts of the world and a similar association between low serum calcium levels and febrile seizures was found [5].…”
Section: Discussionmentioning
confidence: 86%
“…Lower level of calcium, even if not in hypocalcemic range, is associated with occurrence of febrile seizure [12]. Ionized calcium deficiency has been proposed as a risk factor for febrile seizure [13]. A more comprehensive study is needed to determine if serum calcium level affects febrile seizure duration.…”
Section: Discussionmentioning
confidence: 99%
“…During any acute febrile disease, disturbances in water and electrolytes occur frequently. It has been suggested that change in serum calcium might enhance the susceptibility to seizures 1 . A common biochemical abnormality causing seizures is hypocalcaemia, which may manifest as muscle cramps, tetany, seizures and paresthesia 2 .…”
Section: Introductionmentioning
confidence: 99%